Common Proteomic Technologies, Applications, and their Limitations - Meyfour, Anna; Rezaie Tavirani, Mostafa; Sadeghi, Mohammad Reza (Archives of Advances in Biosciences, 2013)
Proteomics refers to the analysis of expression, localization, functions, posttranslational modifications, and interactions of proteins expressed by a genome at a specific condition and at a specific time. Current proteomic tools allow large-scale, high-throughput analyses for the detection, identification, and functional investigation of proteome. In this review, we have focused on the proteomics methods: gel-based and gel-free techniques and discussed their applications and challenges in the field of proteomics.